Controlled Sr(ii) ion release from in situ crosslinking electroactive hydrogels with potential for the treatment of infections - Demirkan, Melike Firlak; Ozturk, Dilek; Cifcibasi, Zeynep Sude; Ertan, Fatma; Hardy, John George; Nurseval Oyunlu, Asli; Darici, Hakan (Royal Soc Chemistry, 2024)
The development of electrochemical stimuli-responsive drug delivery systems is of both academic and industrial interest due to the ease with which it is possible to trigger payload release, providing drug delivery in a controllable manner. Herein, the preparation of in situ forming hydrogels including electroactive polypyrrole nanoparticles (PPy-NPs) where Sr2+ ions are electrochemically loaded for electrically triggered release of Sr2+ ions is reported. The hydrogels were characterized by a variety of techniques including Fourier-transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), X-ray diffraction (XRD), cyclic voltammetry (CV), etc. The cytocompatibility towards human mesenchymal stem cells (MSCs) and fibroblasts were also studied. The Sr2+ ion loaded PEC-ALD/CS/PPy-NPs hydrogel showed no significant cytotoxicity towards human mesenchymal stem cells (MSCs) and fibroblasts. Sr2+ ions were electrochemically loaded and released from the electroactive hydrogels, and the application of an electrical stimulus enhanced the release of Sr2+ ions from gels by ca. 2-4 fold relative to the passive release control experiment. The antibacterial activity of Sr2+ ions against E. coli and S. aureus was demonstrated in vitro. Although these prototypical examples of Sr2+ loaded electroactive gels don't release sufficient Sr2+ ions to show antibacterial activity against E. coli and S. aureus, we believe future iterations with optimised physical properties of the gels will be capable of doing so.
Keywords: Mesenchymal Stem-Cells; Antimicrobial Activity; Metallic-Ions; Pectin; Differentiation; Stimulation; Polymers; Protein